Статистические процедуры при двухстороннем ограничении контролируемого параметра в процессе производства кабельно-проводниковой продукции - Голик, Оксана Вячеславовна (НТУ "ХПИ", 2016)
Рассмотрены вопросы статистического контроля в процессе производства массовой кабельно-проводниковой продукции на примере эмальпроводов. Получены результаты непосредственного контроля диаметра эмальпровода с полиимидной двухслойной изоляцией в непрерывном технологическом цикле. Представлена контрольная карта максимальной вероятности выхода диаметра за пределы определенного диапазона.

Purpose. To consider issues of statistical control in the process of mass production of cable and wire products on the example of enameled wire. To analyze the results of direct control of the diameter of the wire in two-layer polyimide insulation in a continuous technological cycle. To submit to the control map of maximum probability of the exit diameter outside a specific range. To analyze the conditions under which maximum sensitivity of process control. Methodology. Study of the sensitivity of the control map of maximum probability of the exit option for regulatory of limit in the field deviations of the centered parameter close to zero. The existence of stable trends in the change of a controlled parameter can reduce the sensitivity of punishment to instability of the process. Results. To achieve maximum sensitivity of control of the technological frontier should be selected on the basis of the achieved level of the average value of the parameter and its statistical scattering. Process boundaries must be changed in accordance with the achieved level of the average value of the parameter and its statistical scattering. Such a change may serve as a quantitative indicator of trends in the increase or decrease in the reliability of the technological system. Originality. In particular the tasks of current control using engineering tolerances for controlled parameter are impractical. Control on Pmax should be directed to the exception of manufacturing, the parameters of which extend beyond the technical tolerances. Practical value. The exception is the manufacture of bulk cable products, the parameters of which extend beyond the technical tolerances.
Statistical procedures for two-sided limit of a controlled parameter in the process of production of cable and wire products
Keywords: эмальпровод; двойная полиимидная изоляция; контрольная карта; enameled wire; double polyimide insulation; control card